Gatorade International Triathlon Science II Conference (1999)
Summary of the second Gatorade International Triathlon Science Conference which was held in Noosa, 1999. Olympic coaches from New Zealand, USA, Greece, Spain and Australia took part. The main topic was: Maximising Olympic Distance Triathlon Performance Reports were held in the categories - Exercise Physiology - Coaching - Nutrition and fluids - Biomechanics - Psychology